Information and Communication Technologies in Tourism 2018 2017
DOI: 10.1007/978-3-319-72923-7_35
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Digital Technologies in Facilitating Intergenerational Learning in Heritage Tourism

Abstract: This research proposes a framework of intergenerational learning (IGL) that supports child-to-parent influence in the context of heritage learning using augmented reality (AR) and serious game applications. Positioning children as the behavioural catalysts in the learning process, the framework is developed based on several considerations and requirements. First, the technologies are designed to play a role in attracting and engaging children in learning and providing an intergenerational participation structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Since a primary goal was to encourage collaborative conversation rather than didactic instruction, we sent an email to parents/guardians/caregivers a few days prior to the event describing their roles and responsibilities. In particular, we wanted them to become behavioral catalysts (Benckendorff et al, 2018), encouraging them to employ an inquiry behavior by collaborating with the other family(-ies) in their group to mentor and help the children locate information which allowed them to posit answers and construct hypothesis. Also, we suggested that they could provide children with prompts that will enable them to better understand the concepts and clues provided, but that they should resist shutting down conversation by providing the answers to the various tasks.…”
Section: Methodology: Design Testing and Evaluationmentioning
confidence: 99%
“…Since a primary goal was to encourage collaborative conversation rather than didactic instruction, we sent an email to parents/guardians/caregivers a few days prior to the event describing their roles and responsibilities. In particular, we wanted them to become behavioral catalysts (Benckendorff et al, 2018), encouraging them to employ an inquiry behavior by collaborating with the other family(-ies) in their group to mentor and help the children locate information which allowed them to posit answers and construct hypothesis. Also, we suggested that they could provide children with prompts that will enable them to better understand the concepts and clues provided, but that they should resist shutting down conversation by providing the answers to the various tasks.…”
Section: Methodology: Design Testing and Evaluationmentioning
confidence: 99%
“…Digital heritage modeling for documentation, explanation or valorization purposes has grown with the number of sites and objects studied and recognized. New forms of heritage management evolved from the trend towards heritage tourism [18], and similarly, new practices arise from the digital incursion in heritage management [6], [7].…”
Section: Domain Ethical and Methodological Needsmentioning
confidence: 99%
“…Cutler et al present their experiments and learning in authoring interactive VR narratives across different scenarios [15]. Compared to VR, which blocks users from the physical world, AR can enrich story elements by augmenting a physical photo with digital content beside it, which allows storytellers and listeners to access both the physical and digital worlds simultaneously [5,11,27,40,59,65,66,84,87]. Thus, AR technology has the potential to foster collaboration, shared experience, and co-creation in storytelling, which motivated our choice of AR to facilitate the photo-based intergenerational storytelling process.…”
Section: Digital Technologies To Facilitate Photo-based Intergenerati...mentioning
confidence: 99%